2010
DOI: 10.1590/s1677-04202010000200007
|View full text |Cite
|
Sign up to set email alerts
|

Flooding tolerance of tomato genotypes during vegetative and reproductive stages

Abstract: A greenhouse experiment was conducted to investigate the effect of flooding on two tomato cultivars and two wild related species. Forty days old tomato plants were subjected to a continuous flooding stress of different durations: 0, 2, 4 and 8 days. Plant pots were placed inside larger plastic pots; they were irrigated with excessive quantity of tap water at 25 0 C so that the level of water above the surface of soil was 15 cm throughout the flooding period. At the bottom of each plastic pot a drilled hole all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 45 publications
4
38
0
7
Order By: Relevance
“…Thus, the flooded plants between 4 and 8 days showed a delay in growth and development as compared with a shorter stress time (Tables 1 and 2), so the onset of flowering was delayed, considering that the cape gooseberry produces one flower at each node of the reproductive shoots (Fischer, 2000). Also, Ezin et al (2010) found a reduction in the number of flowers and fruits and in the fruit size and weight in the tomato, attributing these results to the inhibition of photosynthesis and the adverse effects of flooding conditions.…”
Section: Number Of Reproductive Organsmentioning
confidence: 85%
See 1 more Smart Citation
“…Thus, the flooded plants between 4 and 8 days showed a delay in growth and development as compared with a shorter stress time (Tables 1 and 2), so the onset of flowering was delayed, considering that the cape gooseberry produces one flower at each node of the reproductive shoots (Fischer, 2000). Also, Ezin et al (2010) found a reduction in the number of flowers and fruits and in the fruit size and weight in the tomato, attributing these results to the inhibition of photosynthesis and the adverse effects of flooding conditions.…”
Section: Number Of Reproductive Organsmentioning
confidence: 85%
“…In studies with flooded tomatoes that applied chlorophyll fluorescence, Ezin et al (2010) and Kläring and Zude (2009) observed that the reduction in photosynthetic rates is related to limitations in the PSII reaction center.…”
Section: Leaf Areamentioning
confidence: 99%
“…Tomato plants had ability to develop adventitious roots which attributed to its tolerance to excess water conditions (Walter et al, 2004). Adventitious root formation compensated for loss of the original roots due to hypoxic condition below water table (Ezin et al, 2010).…”
Section: Slfw and Slwc Were Not Affected By Shallow Water Tablementioning
confidence: 99%
“…Intolerant species undergo leaf chlorosis, as reported by Reyna et al (2003) for soy (Glycine max (L.) Merr.) and Ezin et al (2010) for the tomato (Lycopersicon esculentum Mill. ).…”
Section: Oliveira Akm E Gualtieri Scjmentioning
confidence: 99%
“…Several researchers have studied the effects of flooding during certain periods by considering the morphological, anatomical, physiological and biochemical changes in plants, such as changes in gas exchange (MOMMER et al, 2004;EZIN et al, 2010;SCREMIN-DIAS et al, 2011;KATO;OKAMI, 2011;PARLANTI et al, 2011;among others). Stressed plants adapt to disturbances caused by hypoxia or anoxia in the root have different adaptations; the most common of these adaptation strategies being increased stomatal conductance, reducing photosynthesis, changes in transpiration rates, the inhibition of growth, the wilting and/or abscission of leaves, and reduced leaf water potential (KOZLOWS KI, 1997;WITTMANN, 2010;PAREEK et al, 2010).…”
Section: Introductionmentioning
confidence: 99%